PENGARUH BRAND AWARENESS DAN BRAND TRUST TERHADAP KEPUTUSAN PEMBELIAN PRODUK UMKM DI KOTA KENDARI - Dzulfikri Azis Muthalib (Jurnal Multidisipliner Bharasumba, 2025)
This study aims to analyze the effect of brand awareness and brand trust on purchasing decisions of MSME products in Kendari City.. This research employs a quantitative approach with an explanatory research design. Data were collected through questionnaires distributed to consumers of MSME products in Kendari City, involving 100 respondents selected using a simple random sampling technique. The data were analyzed using multiple linear regression analysis with the assistance of SPSS software. The results indicate that brand awareness and brand trust simultaneously have a positive and significant effect on purchasing decisions of MSME products in Kendari City. Partially, both brand awareness and brand trust also have a positive and significant effect on purchasing decisions, with brand trust identified as the most dominant variable. These findings suggest that consumers tend to purchase MSME products that they are familiar with and trust. This study is expected to contribute theoretically to marketing literature, particularly in the context of MSME brand equity, and to provide practical implications for MSME actors and local governments in formulating effective marketing strategies to enhance the competitiveness of local MSME products.